Formulation and Efficacy Test of Antistress Aromatherapy Candle with Jasmine Essential Oil (Jasminum sambac L) on Mice (Mus musculus) - Febrianti, Noor Alfina; Rahmawati, Riana Putri; Arif, Fahrudin (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: Aromatherapy is a non-pharmacological healing method that uses essential oils as therapeutic agents. Jasmine flowers (Jasminum sambac L.) contain active compounds such as linalool, benzyl acetate, methyl salicylate, cis-jasmone, nerolidol, and indole that have potential applications in stress management. This study aims to investigate the antistress efficacy of aromatherapy candles made from jasmine essential oil on mice (Mus musculus). Research Method: This study employed a laboratory experiment with a post-test-only control group design. A total of 25 male mice were divided into five groups, each consisting of five mice. The treatment groups were exposed to aromatherapy candles with essential oil concentrations of 2%, 4%, and 6%, while the control groups included a negative control and a positive control. Stress induction was performed using the Tail Suspension Test (TST), and effectiveness was assessed through immobility time parameters. Data analysis was conducted using a One-Way ANOVA test. Results and Discussion: The results indicate that the wax formula with a concentration of 6% has the best physical characteristics and provides the fastest relaxation effect. The ANOVA test reveals a significant difference between groups (p < 0.05), indicating a significant effect of aromatherapy wax on stress reduction in mice. Implications: This study reinforces the potential of jasmine essential oil-based aromatherapy candles as an alternative therapy for stress management, while also supporting the development of safe and effective, naturally based health products.